Menstrual Health and Sports Performance Research; Do We Need to Broaden Our Approach? - Dionne A. Noordhof; Georgie Bruinvels; Robert P. Lamberts; Ritva S. Mikkonen (International Journal of Sports Physiology and Performance, 2026)
Background : Interest in menstrual health and sports performance has increased, with the majority of research focusing on females with a eumenorrheic menstrual cycle. Purpose : This invited commentary discusses the need to broaden our approach when conducting menstrual health-related research in physically active and athletic populations. We highlight the current state of research regarding the effect of menstrual cycle phase on performance-determining variables, acute training responses, recovery measures, and performance, and question the benefit of continuing to conduct studies that focus only on the most hormonally distinct eumenorrheic menstrual cycle phases. The high prevalence of menstrual disturbances and hormonal contraceptive use, in addition to the challenges and/or possible impracticality of using gold-standard methods of tracking menstrual cycles, regrettably limits the generalizability of findings. Therefore, we identify several knowledge gaps and propose methodological approaches that may improve our understanding of menstrual health in female athletes and the circumstances under which they train and perform. Conclusions : By broadening our research approach, rather than focusing primarily on eumenorrheic cycles, we can provide female athletes and their support teams with more practically applicable evidence-based information to promote health and performance.